Конкуренція і конкурентоспроможність - Романенко, В.А. (№8, 2007)
The problems of national economy corporatisation and machine building competitive entities formation are reviewed based on machine building industry. The number of action items oriented on internal market protection from transnational corporation expansion is presented.